IMU acceleration data differs between the front and rear foot in snowboard halfpipe - Gorges, T.; Thelen, M.; Merz, C. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to compare acceleration data from front and rear foot IMUs of elite snowboard halfpipe riders to gain insights towards IMU driven motion analysis and event detection. Utilizing IMUs attached to riders' boots, the research found varying time offsets and correlations across different axes. The findings show that IMU placement and orientation play a crucial role in accurately capturing snowboarding dynamics. The study contributes to the potential use of IMU data for enhancing motion analysis and feedback systems in snowboard freestyle.